Association of brain heptachlor epoxide and other organochlorine compounds with lewy pathology. Issue 2 (30th December 2018) - Ross, G. Webster; Abbott, Robert D.; Petrovitch, Helen; Duda, John E.; Tanner, Caroline M.; Zarow, Chris; Uyehara‐Lock, Jane H.; Masaki, Kamal H.; Launer, Lenore J.; Studabaker, William B.; White, Lon R.
ABSTRACT: Background: Organochlorine pesticides are associated with an increased risk of Parkinson's disease. A preliminary analysis from the Honolulu‐Asia Aging Study suggested that heptachlor epoxide, a metabolite from an organochlorine pesticide extensively used in Hawaii, may be especially important. This was a cross sectional analysis to evaluate the association of heptachlor epoxide and other organochlorine compounds with Lewy pathology in an expanded survey of brain organochlorine residues from the longitudinal Honolulu‐Asia Aging Study. Methods: Organochlorines were measured in frozen occipital or temporal lobes in 705 brains using gas chromatography with mass spectrometry. Lewy pathology was identified using hematoxylin and eosin‐ and α‐synuclein immunochemistry‐stained sections from multiple brain regions. Results: The prevalence of Lewy pathology was nearly doubled in the presence versus the absence of heptachlor epoxide (30.1% versus 16.3%, P < 0.001). Although associations with other compounds were weaker, hexachlorobenzene ( P = 0.003) and α‐chlordane ( P = 0.007) were also related to Lewy pathology. Most of the latter associations, however, were a result of confounding from heptachlor epoxide. Neither compound was significantly related to Lewy pathology after adjustment for heptachlor epoxide. In contrast, the association of heptachlor epoxide with Lewy pathology remained significant after adjustments for hexachlorobenzene ( P = 0.013) or α‐chlordane ( P = 0.005). Findings were unchanged after removal of cases of PD and adjustment for age and other characteristics. Conclusions: Organochlorine pesticides are associated with the presence of Lewy pathology in the brain, even after exclusion of PD cases. Although most of the association is through heptachlor epoxide, the role of other organochlorine compounds is in need of clarification. © 2018 International Parkinson and Movement Disorder Society